2007
DOI: 10.1148/radiol.2452061093
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Arterial Diameter Measured with US: Adjunct for US Diagnosis of Biliary Atresia

Abstract: Measurement of hepatic artery diameter can be helpful in the US diagnosis of biliary atresia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
3
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 23 publications
8
71
3
3
Order By: Relevance
“…In concordance with other authors [1,10,11] our patients showed enlargement of the hepatic artery. In a previous study performed in biliary atresia patients, at the diagnosis, mean hepatic artery diameter was 2.2±0.59 mm [1].…”
Section: Discussionsupporting
confidence: 93%
“…In concordance with other authors [1,10,11] our patients showed enlargement of the hepatic artery. In a previous study performed in biliary atresia patients, at the diagnosis, mean hepatic artery diameter was 2.2±0.59 mm [1].…”
Section: Discussionsupporting
confidence: 93%
“…Distinct clinical variants, including BA-associated splenic malformation, isolated, cystic, and cytomegalovirus IgM-positive BA, suggest diverse patterns of disease acquisition [6]. Our group is interested in the role of an arteriopathy in BA etiology and several studies [7][8][9][10][11][12] reinforce such a hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, designing a prototype with vessel diameters similar to those vessels carries important implications. Average diameters of the hepatic and uterine arteries are 4 mm and 5 mm, respectively [24,25]. For the prototype, a flexible silicon tube with a diameter of 5 mm and wall thickness of 1 mm is used for the blood vessel model and 0.9% normal saline is used, along with the Alaris syringe pump, to model the circulatory system.…”
Section: Detecting Hepatic Artery and Uterine Arterymentioning
confidence: 99%